Kompetensi Guru Pendidikan Agama Katolik (Pak) Di Era Milenial Dan Pengaruhnya Terhadap Peningkatan Motivasi Belajar Siswa - Emanuel Haru (Jurnal Alternatif Wacana Ilmiah Interkultural, 2019)
Being a teacher in the millenial era is not an easy profession to run. He/ She has to fulfil many demands. He/ She is challenged to have various competencies. Among those that must be fulfilled are competence in technology part. A teacher in the millenial era must be master in using technology tools,such as computer and internet. At least, a teacher must know to operate basic computer programs. By this way, a learning will take place interesting and effectively. For example, a teacher must be able to present His/ Her subject with power point. Besides, a teacher must be able to use e-mail and several other internet programs which are important to support the learning process. By mastering technology, a teacher is expected to explore many sources of knowledge. Therefore, He/ She hasmore knowledge better than students. In addition, a teacher must also prove his professionalism as a teacher by perform all four competencies namely pedagogical, personal, social and professional competencies. A Catholic Religious Education Teacher must also have such competencies. Apart from those mentioned, one of the typical competencies possessed by Catholic Religious Education Teachers is spiritual competence. By having the competencies as mentioned above, a teacher (including Catholic Religious Education Teachers) is able to increase students’ learning motivation in the entire of learning process in a school. In this article, the writer presents several studies that prove the influence of the competencies of a teacher (including Catholic Religious Education Teacher) on student learning motivation, especially in this millennial era. These studies concluded that the higher competency of a teacher, cause the students have a good motivation in learning. In contrary, the lower competence of a teacher cause the lower motivation of students to learn.For this reason, the Catholic Religious Education Teacher is expected to be able to apply these competencies in the daily learning process so that students’ learning motivation increases and in the end, the students’ learning achievements also increase.